APPLYING TONY BUSH'S EDUCATIONAL MANAGEMENT MODEL TO THE MANAGEMENT OF VIETNAMESE EDUCATIONAL INSTITUTIONS - Bui Van Hung (Tạp chí Khoa học)
The article analyzes the educational management models proposed by Tony Bush and applies them to the context of educational management in Vietnam. Based on an overview of educational management and the critical role of management models in improving the quality of education, the article analyzes in depth the essential elements of educational management models. Based on the current management situation at educational institutions in Vietnam, the article proposes ways to apply each element of the model in practice. It points out necessary adjustments to suit Vietnam's cultural, policy and educational conditions. Finally, the article provides assessments of the effectiveness and challenges of applying this model, along with recommendations to enhance educational management capacity towards sustainable development and meeting the requirements of modern education.